The impact of corruption on SMEs’ access to finance: Evidence using firm-level survey data from developing countries - Amin, Mohammad; Motta, Victor (Journal of Financial Stability, 2023)
The present paper estimates the impact of bureaucratic corruption on access to finance for small and medium enterprises (SMEs) in the manufacturing sectors of 79 developing countries. Corruption can make it difficult for businesses to obtain financing by reducing profits, increasing credit demand, increasing the likelihood of bankruptcy , creating uncertainty about future profits, and exacerbating the asymmetric information problem between borrowers and lenders. Consistent with this viewpoint, our findings show that corruption significantly increases the likelihood of a manufacturing SME being financially constrained. A one standard deviation increase in the prevalence of corruption leads to a 3.5–4.9% point increase in the likelihood or probability of a manufacturing SME being financially constrained. In countries with credit bureaus and more freely functioning credit markets, the increase in the likelihood of being financially constrained due to higher corruption is much smaller. We argue and provide evidence that these heterogeneities stem from the specific ways in which corruption affects SMEs’ access to finance . Thus, the heterogeneities help to raise confidence against the omitted variable bias and reverse causality concerns with our estimation. We also find that higher corruption makes it more difficult for SMEs to access finance in more competitive product markets, as well as for small compared to medium-sized firms. The findings have important policy implications for anti-corruption initiatives, financial development, and the level of competition in product markets.